PENGERTIAN MASAILUL FIQHIYAH AL-HADITSAH SEBAB TERJADINYA DAN TUJUAN MEMPELAJARINYA - Abdul Wahab Syakhrani; Dewi Sinta, Helda Yanti, Herlina, Hini Fatimah (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2023)
Masail Fiqhiyah are problems related to fiqh that are actual in nature. Masailul Fiqhiyah Al Haditsah are new problems that emerged after the revelation of the Qur'an and Hadith after the death of Rasulullah SAW. Masail Fiqhiyah arises due to several factors that influence it. The scope of masailul fiqhiyah al haditsah, namely: 1) Worship of human relations with Allah SWT, 2) human relations with fellow human beings. Masail Fiqhiyah arises due to several factors that influence it. These reasons have been mentioned above. The purpose of Masa'il fiqhiyah in general is to answer and resolve new problems that arise in society in modern life which often become questions that require logical answers regarding legal certainty. While the specific goal of studying Masail Fiqhiyah for us as prospective educators is so that later when teaching we are ready and able to answer and solve problems and questions that may arise from students. New things happen due to different views in understanding religion. In addition, the times are constantly evolving and demanding new interpretations of religion, which of course do not come out of the corridors of Islam. Al-Qur'an with its miracles will always be in accordance with the times and places.